A 3D-mixed ion/electron conducting scaffold prepared by in situ conversion for long-life lithium metal anodes. Issue 5 (2nd February 2021) - Jiang, Huai; Dong, Qingyuan; Bai, Maohui; Qin, Furong; Yi, Maoyi; Lai, Junquan; Hong, Bo; Lai, Yanqing
Abstract : A 3D mixed ion/electron conducting scaffold has been prepared by the in situ conversion of lithiated Cu3 P nanoarrays, which possesses features of ionic/electrical conductivity and structural stability. Abstract : Lithium (Li) metal is widely considered the most promising anode material because of its ultrahigh specific energy. However, the obvious volume change and uncontrollable dendrite growth hinder its commercial applications. Herein, we designed a 3D scaffold of Cu3 P nanoarray-modified Cu foam via in situ conversion (3D MIECS). Uniform lithiophilic Cu3 P nanoarrays were in situ grown inside the Cu foam (Cu3 P NA@CF) that presented a high specific surface area and very low nucleation overpotential. Specifically, the lithiated Cu3 P nanoarrays possess the features of mixed ion/electron conductivity and structural stability responsible for uniform Li deposition in the whole three-dimensional space of the metal skeleton, showing scarcely any volume expansion or structural collapse during the continuous Li plating/stripping process. Therefore, the modified Cu foam host achieves dendrite-free cycling over 600 cycles at a current density of 3 mA cm −2 with a coulombic efficiency (CE) of 99.1%. A 3D MIECS-Li||LiFePO4 full cell holds a capacity retention of 80% with a stable CE of 99.63% over 1000 cycles at 3 C.